2014
DOI: 10.1063/1.4854976
|View full text |Cite
|
Sign up to set email alerts
|

Study of plasma meniscus and beam halo in negative ion sources using three dimension in real space and three dimension in velocity space particle in cell model

Abstract: Our previous study by two dimension in real space and three dimension in velocity space-particle in cell model shows that the curvature of the plasma meniscus causes the beam halo in the negative ion sources. The negative ions extracted from the periphery of the meniscus are over-focused in the extractor due to the electrostatic lens effect, and consequently become the beam halo. The purpose of this study is to verify this mechanism with the full 3D model. It is shown that the above mechanism is essentially un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…This beam halo was considered to have large divergence angles in comparison with the beam core region, while the origin of the beam halo is unclear. Therefore, the mechanism of the formation of the beam halo is being studied experimentally [6] and theoretically [7]. Recently, detail particle-in-cell (PIC) simulations suggested that beam halo is formed by non-uniformity of ion current caused by difference on the extraction route of produced negative ions depending on the position of their production on a plasma grid (PG) [8][9].…”
mentioning
confidence: 99%
“…This beam halo was considered to have large divergence angles in comparison with the beam core region, while the origin of the beam halo is unclear. Therefore, the mechanism of the formation of the beam halo is being studied experimentally [6] and theoretically [7]. Recently, detail particle-in-cell (PIC) simulations suggested that beam halo is formed by non-uniformity of ion current caused by difference on the extraction route of produced negative ions depending on the position of their production on a plasma grid (PG) [8][9].…”
mentioning
confidence: 99%
“…The potential is constant or slowly varies in most of the volume inside the reservoir. Similar meniscus studies were also performed [15,25,26] but for fusion sources. The importance of the plasma screening effect on the NI extraction can be easily seen in figure 8, where the NI trajectories are represented for two cases, for the extraction of the source IS01.…”
Section: Plasma Screeningmentioning
confidence: 86%
“…One of the most important factors that determines the beam focusing is the formation of a plasma meniscus, which is the boundary between the source plasma and the beam [21,22]. The meniscus is physically defined as the equipotential surface, where the quasi-neutrality is broken [23,24]. The meniscus plays a role of an electrostatic lens for the first stage of the beam acceleration.…”
Section: Introductionmentioning
confidence: 99%